67 Delay-onset Paraquat-induced Keratoconjunctivitis in a farmer. (11th October 2013) - Lin, WY; Chen, K H; Wu, M T; Yu, M L; Chuang, H Y; Dai, C Y; Li, C H; Chang, N C; Yang, J F; Hsieh, M H; Wang, C L; Huang, C F; et al.
Abstract : Background: Paraquat (dipyridylium herbicide), used commonly in Taiwan, may cause severe pulmonary injury and lung fibrosis and be associated with Parkinsonism. Ocular exposure had caused acute, severe and prolong conjunctivitis with persistent fibrosis, pannus and vascular distortion due to superoxide radicals formation and NADPH depletion via redox cycling reaction as David McKeag's and others' cases . We will report a case with delay onset and relative better prognosis. Case: A 31 years old male farmer had his left eye spilled by Paraquat solution during preparing procedure on Sep 11, 2012. After washing eye by himself with clean water for about 5 minutes, no discomfort was noted initially. Unfortunately, he suffered from pain and tearing 3 days later. Mild conjunctivitis with slight reddish was noted in Ophthalmology Clinic. Focal steroid and antibiotics were used. Progressive worsening condition with more tearing, ocular pain, photophobia, erythematous hyperaemic change, discharge, eyelid swelling, vascular congestion, more papilla and follicles and infiltration had been noted since the 4 th day. Eventually, local pulse steroid every day, focal steroid ointment every 2 hours and oral antioxidant were administered on the impression of Paraquat-associated keratoconjunctivitis caused by superoxide radical on 6 th day. Pseudomembrane formation was found on 8 th . Condition was improving after intensive therapy. Symptoms subsided on 12 th day and papillae, follicles and infiltration disappeared on 18 th day. Only mild dry eye sensation, cicatrization on conjunctiva and no impairment of visual acuity were found 45 days later. No systemic effect could be found. Conclusion: Delay onset is different from acute severe conjunctivitis in McKeag's and other chemical and pesticide exposured ocular injuries. More intense therapy with local pulse steroid and oral antioxidant may improve prognosis with less sequelae. Close monitoring, early management should be considered in case of ocular exposure to Paraquat solution even without early symptom/sign.